THE 2024 INDONESIAN PRESIDENTIAL CANDIDATES’ DEBATE: RHETORICAL AND POSITIVE DISCOURSE ANALYSES - Nasihah, Durotun; Ni’mah, Dzurriyyatun (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
The 2024 Indonesian presidential debate provided a unique platform for candidates to communicate their visions for the country's future. As part of the campaign process, presidential debates serve as a key mechanism for influencing voter perceptions through persuasive rhetoric. This study explores the use of positive language and discursive strategies by Indonesian presidential candidates in the 2024 presidential debate, focusing on how their rhetoric promotes hope, empowerment, and social change. The study analyzes speeches from the five presidential candidates, employing positive discourse analysis (PDA) to identify and interpret key strategies used to engage voters with optimism and progressive visions. The analysis revealed six primary rhetorical strategies: identifying national problems, expressing commitment to societal welfare, framing government roles through metaphors, managing public emotion with narratives, empowering society, and articulating policies through structured argumentation. These strategies were crucial in constructing a discourse of hope and change, aiming to persuade voters of each candidate’s ability to address Indonesia’s pressing issues. For example, Anies Baswedan used metaphors and narratives based on his governance experience, while Prabowo Subianto emphasized his military background and commitment to solving social issues. Ganjar Pranowo focused on empowering society and detailing policy frameworks to foster societal well-being. By highlighting these strategies, the research contributes to understanding the role of political rhetoric in shaping voter perceptions, particularly in multi-candidate debates. The study underscores the importance of language as a tool for political leaders to inspire hope and influence public opinion. This research also advances the field of positive discourse analysis by applying it to political communication in Indonesia, offering valuable insights into how rhetorical strategies can foster collective agency and a brighter future for society. Future research could extend this analysis to other political or cultural contexts, exploring the influence of these strategies on voter behavior and the wider implications of positive discourse in political settings.